2020
DOI: 10.1001/jama.2020.3565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biomechanical Footwear on Knee Pain in People With Knee Osteoarthritis

Abstract: IMPORTANCE Individually calibrated biomechanical footwear therapy may improve pain and physical function in people with symptomatic knee osteoarthritis, but the benefits of this therapy are unclear. OBJECTIVE To assess the effect of a biomechanical footwear therapy vs control footwear over 24 weeks of follow-up. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial conducted at a Swiss university hospital. Participants (N = 220) with symptomatic, radiologically confirmed knee osteoarthritis were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…All patients were treated with a non-invasive biomechanical foot-worn device that aims to treat patients with MSK conditions by center of pressure manipulation and perturbation training to challenge and train neuromuscular control (17).…”
Section: Methodsmentioning
confidence: 99%
“…All patients were treated with a non-invasive biomechanical foot-worn device that aims to treat patients with MSK conditions by center of pressure manipulation and perturbation training to challenge and train neuromuscular control (17).…”
Section: Methodsmentioning
confidence: 99%
“…One crossover RCT (n ¼ 24) of three types of knee braces worn for 3 months each found an unloader brace with both valgus and external rotation functions to be more comfortable and to decrease KAM both at baseline and after treatment (with brace donned), however interpretation of the results are limited by a carryover effect 86 . An RCT investigating footwear with individually adjustable external convex pods attached to the outsole (compared to control shoes) showed reduced pain in the treatment group of limited clinical relevance and mildly increased velocity and step length compared to controls 87 . An RCT of minimalist footwear in women with knee OA that had previously shown reduced KAM and KAM impulse after 6 months 88 conducted secondary analyses to explain the mechanism of reduction of KAM 89 .…”
Section: Biomechanics In Oa Treatmentmentioning
confidence: 99%
“…Furthermore, there are many different types of physical therapies that are recommended for OA. Recently, a randomized clinical trial from Stephan et al (Reichenbach et al, 2020) compared the effects of biomechanical footwear and control footwear on relieving OA pain. Their results showed that biomechanical footwear resulted in an improvement in pain at 24 weeks of follow-up that was statistically significant but of uncertain clinical importance.…”
Section: Clinical Studiesmentioning
confidence: 99%